The altars of Republican Rome and Latium : sacrifice and the materiality of Roman religion - Moser, Claudia (Cambridge University Press, 2019)
This book reorients the study of sacrifice, examining the locus of ritual action - the altars of Republican Rome and Latium.
Keywords: Almanah ṿeha-aḥim Rom; Rites and ceremonies -- Rome.; Sacrifice -- Rome.; Altars -- Rome.; Rites et cérémonies -- Rome.; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Antiquities & Archaeology.; Altars; Rites and ceremonies; Sacrifice; Rome (Empire); Altar; Materialität; Opferritus; Römerzeit; Latium